The genetic diversity and differentiation of narrow-clawed crayfish Pontastacus leptodactylus (Eschscholtz, 1823) (Decapoda: Astacidea: Astacidae) in the Caspian Sea Basin, Iran as determined with mitochondrial and microsatellite DNA markers. Issue 2 (26th February 2019) - Khoshkholgh, Majidreza; Nazari, Sajad
Abstract: We investigated the genetic structure of seven populations of the narrow-clawed crayfish Pontastacus leptodactylus (Eschscholtz, 1823 ) from the Caspian Sea basin, Iran by partial sequencing of the control region (D-loop) of the mitochondrial DNA (mtDNA) and 10 microsatellites. Mitochondrial DNA sequences revealed significant haplotype diversity (0.811 ± 0.049) and nucleotide diversity (π) (0.0127 ± 0.0038) along the Astara region, Siah Darvishan and Chafrood rivers. Significant deviations from Hardy-Weinberg equilibrium within populations were detected for most populations in the screened microsatellite loci. The two types of markers were particularly informative in delineating population structure of P. leptodactylus . Analyses of molecular variance (AMOVA) showed significant genetic differentiation ( P < 0.05) between populations for both microsatellite and mtDNA markers. At least three genetically distinct management units were observed using the two methods among the sampling sites investigated. Analyses of both genomes provided high resolution and confidence in characterizing the population structure of P. leptodactylus . The results are consistent with the findings from PCR-RFLP analysis and suggest considerable genetic diversity of the populations from the Caspian Sea basin. These results could give applicable information for the cultivation of stocks and also for future genetic improvement of this commercial species by a selective breeding program.